Perubahan Perilaku Sosial Siswa SD di Era Digital dan Implikasinya terhadap Pembelajaran IPS: Kajian Literatur - Laila, Suci; Fauziah, Aklil; Adrias (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The digital age has brought about fundamental changes in the social behavior patterns of elementary school students, particularly in terms of interaction, communication, and character development. This systematic literature review aims to (1) analyze the forms and causal factors of changes in the social behavior of elementary school students in the digital age, (2) examine their impact on Social Studies (IPS) learning, and (3) formulate implications for relevant Social Studies learning strategies. The method used is a Systematic Literature Review (SLR) following the PRISMA guidelines, involving a search of articles from Google Scholar, Garuda, and DOAJ spanning 2015–2025. The findings indicate that the widespread use of digital technology has led to a shift from face-to-face interactions to virtual interactions, a decline in empathy and social skills, and the emergence of online aggressive behavior. This has an impact on the reduced effectiveness of instilling social values in social studies learning. Consequently, social studies teachers need to integrate technology-based approaches such as cooperative learning supported by digital media, critical digital literacy, and contextual approaches that link social studies material to students’ real lives.